Pengembangan LKPD Berbasis Inquiry Project Task Untuk Meningkatkan Keterampilan Proses Sains Siswa Kelas IV - Sry Mulyani Tarigan; Bramianto Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to produce and determine the results of feasibility and effectiveness tests on Inquiry Project Task Based Student Worksheets (LKPD) to improve the science process skills of class IV elementary school students. This research was conducted in class IV at SDN Jayamukti 04, Kab. Bekasi. The type of research used is research and development with the ADDIE development model. The development process went through validation tests by 3 experts, responses from 33 class IVB students and 1 class teacher. Based on the research results, 85.45% of the media validation test results were obtained, 88.57% of the language validation test results, 100% of the material validation test results were in the very feasible category. Meanwhile, the results of data analysis from teacher and student response questionnaires obtained an average result of 91.27% with very practical criteria. From the results of these data it can be concluded that the Inquiry Project Task Based Student Worksheet (LKPD) is suitable for use as a learning medium to support the teaching and learning process on science material with the theme of animal life cycles for fourth grade elementary school students.